2016
DOI: 10.1016/j.psi.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Social Network to Protective Factors in Suicide and Alcohol Use Disorder Intervention for Rural Yup’ik Alaska Native Youth

Abstract: Suicide and alcohol use disorders are significant Alaska Native health disparities, yet there is limited understanding of protection and no studies of social network factors in protection in this or other populations. The Qungasvik intervention enhances protective factors from suicide and alcohol use disorders through activities grounded in Yup’ik cultural practices and values. Identification of social network factors associated with protection within the cultural context of these tight, close knit, and high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Whitbeck (R01-DA037177–01 A1) is planning on using measures of Indigenous family influences and cultural processes. Mishra (1R01-CA192967) plans on utilizing items from prior studies to measure the following constructs: social norms and support; socio-ecological level variables, such as social norms and health access; cultural influences on colorectal cancer screening; and social network assessment (Philip, Ford, Henry, Rasmus, & Allen, 2016). Walters et al (2018) provides a more thorough overview of Indigenous-based theoretical constructs and theories utilized in the development of culture-centered interventions from the ground-up (refer to Walters et al, 2018, in this Special Edition Journal).…”
Section: Gathering the Medicine (Results)mentioning
confidence: 99%
“…Whitbeck (R01-DA037177–01 A1) is planning on using measures of Indigenous family influences and cultural processes. Mishra (1R01-CA192967) plans on utilizing items from prior studies to measure the following constructs: social norms and support; socio-ecological level variables, such as social norms and health access; cultural influences on colorectal cancer screening; and social network assessment (Philip, Ford, Henry, Rasmus, & Allen, 2016). Walters et al (2018) provides a more thorough overview of Indigenous-based theoretical constructs and theories utilized in the development of culture-centered interventions from the ground-up (refer to Walters et al, 2018, in this Special Edition Journal).…”
Section: Gathering the Medicine (Results)mentioning
confidence: 99%
“…The results of the present study support the view that SS is one of the strongest protective factors against stressful events, and that it enables individuals to implement effective coping behaviours (Park, Wang, Williams, & Alegría, 2018). Authors such as Cohen and Syme (1985) or Philip, Ford, Henry, Rasmus, and Allen (2016) have suggested that SS may intervene in stressful life events by attenuating stress appraisal responses, thus buffering negative experiences and empowering and strengthening the individual through successful coping experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Positive relationships provide emotional support resources, information and instrumental help that facilitate coping with stress and promote psychological well-being and quality of life. As shown in two studies with this approach, social networks are a protective factor against suicide and alcohol abuse in a native community of Alaska (Philip, Ford, Henry, Rasmus, & Allen, 2015), while informal support resources are among the most important community assets of Asian Americans living in Florida (Weng, 2015). Let us look more closely the contributions of the monograph.…”
Section: Overview Of the Issuementioning
confidence: 99%
“…Furthermore, it follows a method characterized by generating a fixed number of contacts in each respondent (McCarty, 2002), which has proved efficient in analyzing the structures of personal networks. This approach is an evolution of the studies of social support, to which the work of Philip et al (2015) and Weng (2015), also published in Psychosocial Intervention, are closer.…”
Section: Bridging the Science-practice Gap Personal Network And Socmentioning
confidence: 99%